To solve the quadratic equation \( x^2 - 6x - 20 = 20 \) by completing the square, follow these steps:
-
Move the constant to the right side: \[ x^2 - 6x - 20 - 20 = 0 \ x^2 - 6x - 40 = 0 \ x^2 - 6x = 40 \]
-
Complete the square: Take half of the coefficient of \( x \) (which is -6), square it, and add it to both sides: \[ \left(-\frac{6}{2}\right)^2 = 9 \] So we add 9 to both sides: \[ x^2 - 6x + 9 = 40 + 9 \ x^2 - 6x + 9 = 49 \]
-
Rewrite the left side as a squared term: \[ (x - 3)^2 = 49 \]
-
Take the square root of both sides: \[ x - 3 = \pm 7 \]
-
Solve for \( x \): \[ x - 3 = 7 \implies x = 10 \ x - 3 = -7 \implies x = -4 \]
Thus, the solutions are: \[ x = 10, \quad x = -4 \]
So the correct answer is: x=10, x=−4